2018
DOI: 10.1002/hed.25184
|View full text |Cite
|
Sign up to set email alerts
|

Cervical necrotizing fasciitis: Systematic review and analysis of 1235 reported cases from the literature

Abstract: Physicians and surgeons must be vigilant of the diagnosis of cervical necrotizing fasciitis as early clinical findings may be subtle and prompt identification to facilitate aggressive intervention is required to preclude catastrophic local and systemic morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
1
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(157 citation statements)
references
References 52 publications
8
135
1
13
Order By: Relevance
“…Under such circumstances, early tracheotomy is recommended because it is more secure and allows the patient to be moved to a non-critical care unit at an earlier stage, thus reducing the overall costs. [19][20][21] Consistent with the reports by Ridder et al 2 and Palma et al, 22 no secondary infections were observed at the tracheostomy sites in the patients included in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Under such circumstances, early tracheotomy is recommended because it is more secure and allows the patient to be moved to a non-critical care unit at an earlier stage, thus reducing the overall costs. [19][20][21] Consistent with the reports by Ridder et al 2 and Palma et al, 22 no secondary infections were observed at the tracheostomy sites in the patients included in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Among deep neck space infections, type I NSTI predominate [69]. The most important pathogens are viridans streptococci, staphylococci and Gram-negative anaerobes such as Bacteroides fragilis, Prevotella, Fusobacterium and Peptostreptococci [69e71].…”
Section: Microbiologymentioning
confidence: 99%
“…In mediastinitis secondary to DNM, empirical antimicrobial therapy should cover those aerobic and anaerobic bacteria commonly associated with ear, nose and throat infections. Although there are no standardized regimens described in the academic literature, a third-generation cephalosporin with metronidazole [21] or a combination of piperacillin/tazobactam and clindamycin is suggested [56].…”
Section: Antimicrobial Therapymentioning
confidence: 99%